THE IMPORTANCE OF TRADITIONAL ECOLOGICAL KNOWLEDGE TAUGHT IN RURAL PRIMARY SCHOOL - Sumarwati Sumarwati; Atikah Anindyarini (Universitas Sebelas Maret, 2017)
Urban people was rich with traditional culture, like folktales, and traditional ceremonies. It was valuable as traditional ecological knowledge (TEK), but people had been forgotten. The integration of TEK into learning in s primary school may be a key tool for the the potential to improve the delivery of educational objectives about science. This paper explores perceptions about using of the value of TEK into formal education, especially in rural primary school. We conducted interviews with 52 participants (educators, officials, and local TEK experts) regarding the use of the formal school system to transmit, maintain, and revitalise TEK in Tawangmangu, Karanganyar District. Participants reported that TEK in Tawangmangu had eroded and identified the formal school system as a principal driver. Most interviewees believed that if an appropriate format could be developed, TEK could be included in the formal education system. Such an approach has potential to maintain customary knowledge and practice in the focus communities. Participants identified several specific domains for inclusion in school curricula, including diversity of food knowledge, agricultural knowledge and practice, especially corn and vegetables, and the reinforcement of respect for traditional authority and values. TEK has potential to add value to formal education in primary school in Tawangmangu by contextualizing the content and process of learning, and by facilitating character development and self-awareness in students. These benefits are relevant with UNESCO-mandated goals for curricular reform and provide a strong argument for the inclusion of TEK in formal school. However, interviewees also noted a number of practical barriers to teaching TEK in primary school. These relates the cultural diversity and views within the community. However, needed further research to the significant epistemological challenges inherent in including TEK in formal school, particularly as participants noted the potential for such approaches to have negative consequences.